Processing Speed in Children from 6 to 11 Years Old with Autism Spectrum Disorder included in Regular Basic Education - Dioses-Chocano, Alejandro (2022)
Autism Spectrum Disorder (ASD) is considered a neurodevelopmental disorder, whose prevalence has increased in recent years, showing in some cases deficits in the cognitive area, with processing speed (PS) being one of the affected variables. Therefore, the present study aims to: 1) compare the scores obtained in relation to the PS variable between students aged 6 to 11 with ASD and their peers with neurotypical development in Metropolitan Lima; and 2) establish the PS profile of the included students with ASD. For this, 30 children aged 6 to 11 attending to regular basic education institutions (RBE) in Metropolitan Lima were sampled, 15 with neurotypical development and 15 included with ASD. For the first objective, a case-control design (CCD) was used, while the second objective was a selective non-probabilistic cross-sectional design. Results showed a lower performance by the group with ASD in the PS tasks evaluated, compared to their neurotypical peers, as well as differences were found among the children in the group with ASD, which could be associated with the variety of skills that the tasks involved chores.